Galaxy bias and σ8 from counts in cells from the SDSS main sample. (22nd August 2020) - Repp, Andrew; Szapudi, István
ABSTRACT: The counts-in-cells (CIC) galaxy probability distribution depends on both the dark matter clustering amplitude σ8 and the galaxy bias b . We present a theory for the CIC distribution based on a previous prescription of the underlying dark matter distribution and a linear volume transformation to redshift space. We show that, unlike the power spectrum, the CIC distribution breaks the degeneracy between σ8 and b on scales large enough that both bias and redshift distortions are still linear; thus, we obtain a simultaneous fit for both parameters. We first validate the technique on the Millennium Simulation and then apply it to the Sloan Digital Sky Survey main galaxy sample. We find σ8 = 0.92 ± .08 and b = 1.39^+.11_-.09 consistent with previous complementary results from redshift distortions and from Planck.